PENGALAMAN SEORANG PETUGAS KEAMANAN (SATPAM) AKPER DHARMA HUSADA KEDIRI SEBAGAI FIRST RESPONDER DALAM MENOLONG KORBAN KECELAKAAN LALU LINTAS - R, Elfi Quyumi; Novita, Novita (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2018)
Emergency conditions can occur anytime and anywhere, and can happen to anyone and can not be predicted in a timely manner. Some of the incidents that cause emergency situations are transportation accidents (traffic) (Pusponegoro, 2011). Traffic accidents may result in casualties that may result in grave injuries and may result in fatalities. The casualties caused by traffic accidents are the productive age of the average under the age of 44-45 years.This study explores the experience of security officers (security guards) as first responder at the scene of the accident by using a hermeneutic interpretive phenomenology approach. Participants in this study are security officers (security guards) who duty in Akper Dharma Husada Kediri who had become first responder (first helper) traffic accident victims. Sampling technique by purposive sampling. The instrument in this study is the researcher himself who acts as an instrument. Supporting instrument in this research is netbook equipped with camtasia studio recorder program and stationery which consist of paper and ballpoint pen. The experience of the security guard as the first responder in helping the traffic accident victims was found to mean that the security guard worked and was responsible for saving the victims of the accident on the basis of duty and humanity. The security guard strives to the maximum extent possible in helping the victim despite facing several problems in carrying out his     duties especially related tothe provision of help to the victim. Problems encountered related to the ability and completeness of equipment and cooperation with health workers. This indicates that the implementation of the Integrated Emergency Management System (SPGDT) program has not been well implemented. So for the future should be considered to increase the empowerment of security officers (security guards) as a vanguard who often visit the accident victims first. Despite the many difficulties, the police still feel proud and happy and gratitude can help others. The police have hope to provide the best service to the community. the police also need an appreciation for their maximum efforts in helping victims of accidents